Modos de compartilhamento dos grupos de legendas: utilização das redes sociais e dos dispositivos da cultura digital para a produção de legendas artesanais. - Mendonça, Bruno Henrique Marques de (2014)
This research looks at the Legend Groups and Fansubs - fan organizations that are responsible for the artisan production of subtitles for non-lusophone films, series and other audiovisual productions, sharing their work with other fans through the internet. The main objective is to understand how the relations of production, sharing and circulation of the work that the groups intend to do are given. The methodology adopted contemplates the bibliographic revision of the subjects that orbit around the main theme and the observation and analysis of the empirical objects - the productive chain of the Legend Groups, contemplating sites, repositories - like Legendas.tv -, virtual pages, discussion groups and profiles of social networking sites - in order to understand how to take every step of the process of producing and sharing amateur subtitles. To describe the creation of fansubs and to contextualize them, texts of Cristiane Sato (2005, 2007) and Sean Leonard (2004) are used in order to understand the origin and evolution of fan groups that produce subtitles. The work of these groups is analyzed from the perspective of the concept of division of labor, coined by Adam Smith (2011) and also by the bias of the hacker culture, described by Pekka Himanen (2001), establishing a comparison of the modus operandi of the groups that now are similar to a formal institution, or to reveal their libertarian and alternative ideals related to the concept of work. Henry Jenkins' postulates (1992, 2006, 2009) are used to describe the culture of the fans. Contextualization on translation - as office and study - is presented by authors who discuss their history and their theories. The research advances in order to demonstrate how the process of subtitling of audiovisual materials takes place. In this context, Bakhtin's theory of enunciation, used as a theoretical reference, stands out in the understanding of the meanings of statements in counterpoint to literal word-for-word translations; the theories presented by linguists Luiz Antônio Marcuschi (2010) and Ingedore Koch (2012) in relation to the transformation of oral language into written language and texts by Sabine Gorovitz (2006), which describe the role of subtitles in audiovisual products. Finally, for the purpose of analysis, comparisons are made between legends produced by the LegendisSubs group for the series of The Newsroom (2013) in relation to the institutional legends present in the commercially released DVD and the communication channels that the groups use for the dissemination are presented of your products and for the relationship with your audience. It is concluded that the production of the Legend Groups, even if performed by delegitimized individuals - that is, non-professionals - fulfills the auxiliary role of the spectator, highlighting, mainly, the factor that the producer is knowledgeable of the material to be subtitled, possessing a vast repertoire and even affection for audiovisual material, resulting in a material with information and references that could not be found in the legends performed by legitimate companies and studios.